2008
DOI: 10.1534/genetics.107.085696
|View full text |Cite
|
Sign up to set email alerts
|

The Rad52 Homologs Rad22 and Rti1 ofSchizosaccharomyces pombeAre Not Essential for Meiotic Interhomolog Recombination, but Are Required for Meiotic Intrachromosomal Recombination and Mating-Type-Related DNA Repair

Abstract: Proteins of the RAD52 epistasis group play an essential role in repair of some types of DNA damage and genetic recombination. In Schizosaccharomyces pombe, Rad22 (a Rad52 ortholog) has been shown to be as necessary for repair and recombination events during vegetative growth as its Saccharomyces cerevisiae counterpart. This finding contrasts with previous reports where, due to suppressor mutations in the fbh1 gene, rad22 mutants did not display a severe defect. We have analyzed the roles of Rad22 and Rti1, ano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 82 publications
2
36
0
Order By: Relevance
“…This indicates that the large majority of meiotic intrachromosomal events in the wild type derive from DSBs formed by Rec12. It had been shown before that deletion of the S. pombe RAD52 homologs rad22 and rti1 affected recombination between homologous chromosomes only slightly (maximal 2.5-fold reduction) but reduced prototroph formation in the PS1 assay 80-fold (50). In the VL1 assay the ppm reductions were 7-fold (rad22⌬), 1.9-fold (rti1⌬), and 14-fold (rad22⌬ rti1⌬).…”
Section: Hop1 and Mek1 Proteins Contribute To Homologous Pairingmentioning
confidence: 90%
See 1 more Smart Citation
“…This indicates that the large majority of meiotic intrachromosomal events in the wild type derive from DSBs formed by Rec12. It had been shown before that deletion of the S. pombe RAD52 homologs rad22 and rti1 affected recombination between homologous chromosomes only slightly (maximal 2.5-fold reduction) but reduced prototroph formation in the PS1 assay 80-fold (50). In the VL1 assay the ppm reductions were 7-fold (rad22⌬), 1.9-fold (rti1⌬), and 14-fold (rad22⌬ rti1⌬).…”
Section: Hop1 and Mek1 Proteins Contribute To Homologous Pairingmentioning
confidence: 90%
“…In S. pombe loss of core HR functions leads to very low spore viability: deletion of rad51 but not of dmc1 (20), double mutation of rad54 and rdh54 (7), inactivation of the endonuclease activity encoded by mus81 and eme1 (5,52), and combined deletion of rad22 and rti1 (homologs of RAD52 of S. cerevisiae). But, differently from the other core functions, Rad22 and Rti1 are not required for CO and NCO (50).…”
mentioning
confidence: 99%
“…Rad55 and Rad57 play a minor role in both interhomolog and intrasister exchanges at DSB-poor regions, while Rad52/Rti1 are implicated primarily in intrasister events (Akamatsu et al 2003;Octobre et al 2008;Hyppa and Smith 2010). We constructed double mutants to investigate whether rad16-249 could be placed genetically in either of these pathways.…”
Section: Xpf Required For Meiosis and Genome Stability 1463mentioning
confidence: 99%
“…In addition, our data indicate that Rad22 plays a negative regulatory role in Dmc1-driven strand exchange in contrast to its well-known positive role in Rad51-driven HR. Octobre et al (2008) have shown that Rad22 promotes intersister HR during meiosis in S. pombe and is not required for the production of interhomolog crossover recombinants. On the other hand, interhomolog recombinants are generated from DSB-cold regions in a Dmc1-dependent manner (Hyppa and Smith 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Rad22 plays dual roles in regulating meiotic recombination: activating Rad51 and inhibiting Dmc1. Rad22 is important during meiosis in S. pombe for intersister HR, which leads to noncrossover recombinants, presumably by promoting DNA double-strand break (DSB) repair (Cromie et al 2006;Octobre et al 2008). On the other hand, crossover recombinants (i.e., via interhomolog HR) are produced from DSB-cold regions in a Dmc1-dependent manner (Hyppa and Smith 2010).…”
mentioning
confidence: 99%